Analysis of Service Quality at Maxx Coffee Lippo Plaza Kupang Using the Service Quality (Servqual) Method - Debry F. Pingakh; Semlinda Juszandry Bulan (Jurnal Manajemen Informatika & Teknologi, 2026)
Service quality is an essential factor that influences customer satisfaction and loyalty, especially in service-based businesses such as coffee shops. This study aims to analyze the service quality of Maxx Coffee Lippo Plaza Kupang using the Service Quality (SERVQUAL) method, which includes five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. Data were collected through questionnaires and analyzed using a gap analysis between customer expectations and perceptions. The results show that four dimensions have negative gap values (tangibles, reliability, responsiveness, and assurance), while the empathy dimension has a positive value (0.07). Overall, the service quality value (Q > 1) indicates that the services at Maxx Coffee Lippo Plaza Kupang are considered good.